Difference in Knowledge regarding Reproductive Health and HIV/AIDS between Students in Natural Sciences Major and Social Sciences Major - Juniasti, Helen Try; Asriati, Asriati (Poltekita : Jurnal Ilmu Kesehatan, 2024)
Knowledge regarding HIV/AIDS in Papua among adolescents is still very limited, while there is a 3% HIV prevalence among adolescents. This study aims to determine the difference in knowledge regarding reproductive health and HIV/AIDS between students in Natural Sciences major and Social Sciences major at urban and rural senior high schools in Papua Province. This was a cross-sectional study. The Slovin formula was applied for sample calculation to obtained a total sample of 159 students in Natural Science and Social Sciences majors at SMA Negeri 4 of Jayapura City and SMA Negeri 1 of Keerom District in Papua Province. The study samples were selected using a purposive sampling technique. Statistical tests in this study applied the Mann-Whitney test. The results of the study showed that there was a difference in the level of knowledge regarding HIV/AIDS between students in the Natural Sciences major and Social Sciences major at urban and rural senior high schools (p=0.003). It can be concluded that the level of knowledge of students in natural Sciences majors was higher than that of students in natural Sciences majors at urban and rural senior high schools. Students in Natural Sciences major had a more positive attitude towards HIV/AIDS prevention than students in Social Sciences major studies at urban and rural senior high schools. It is expected that further researchers can develop research variables and research subjects as well as research methods to explore the topic related to the incidence of HIV/AIDS among adolescents.